Topical Collection: Determining groundwater sustainability from long-term piezometry in Sub-Saharan Africa - (:unkn) unknown (My University, 2019)
In Sub-Saharan Africa, groundwater use is a vital strategy to meet rapid increases in freshwater demand projected this century and to adapt to the region's substantial variabilities in rainfall and surface water resources, amplified by climate change. Four studies are considered, which constitute a topical collection of articles that provide new insight into the characteristics and processes by which groundwater is replenished, using recently compiled long-term groundwater-level records together with evidence from satellite data of the sustainability of exploited aquifer systems.
Keywords: African Research